Effect of leaf trichomes and meteorological parameters on population dynamics of aphid and jassid in cotton (Bangladesh Journal of Agricultural Research, 2017)
This study was conducted with CB1, CB3, CB5, CB8 and C12 cotton varieties to determine the role of leaf trichomes and meteorological factors on the abundances of aphid and jassid. The mean population of the pests on the tested varieties differed significantly and showed negative correlation with trichomes. The pests were most abundant on CB12, and each variety revealed significantly higher population of jassid than that of aphid. Both the pests built up their population in the juvenile stage of the plants (73 days after sowing) and continued until harvesting. Aphid population was the highest on CB12 in the first week of November, whereas maximum abundance of jassid was on CB12 in the third week of December. Weather parameters were found insignificant on aphid abundance, but jassid population on the varieties was correlated with maximum and minimum temperatures, relative humidity and rainfall. Multiple regression equation based on weather parameters exerted 8.8 - 43.2% and 54.4 - 77.7% role on population build up of aphid and jassid, respectively. Maximum temperature had the most important effect which contributed 61.2% population fluctuation of jassid on CB12.Bangladesh J. Agril. Res. 42(1): 13-25, March 2017